Perkawinan Beda Agama dalam Perspektif Hak Asasi Manusia - Juri Adrianto (Syntax Corporation Indonesia, 2024)
Interfaith marriages in Indonesia continue to be an issue, with ongoing social and legal discrimination, against couples who enter into such arrangement. This paper discusses the challenges faced by Undang-Undang No. 1 of 1974 on Marriage, along with its amendments in Undang-Undang No. 16 of 2019, in adhering to the principles of human rights. This study employs a literature review approach to examine how the government, through existing legal substance and structure, can ensure legal certainty, legal justice, and legal benefits for interfaith married couples.